Financial Statement Fraud from the Perspective of the Fraud Hexagon Theory - Ivana Gratia; Siti Nur Hadiyati (DINASTI RESEARCH, 2026)
This study aims to examine the effect of fraud hexagon elements, namely pressure, opportunity, rationalization, capability, ego, and collusion, on financial statement fraud in mining companies listed on the Indonesia Stock Exchange during 2022–2024. This study employed a quantitative approach using secondary data obtained from annual financial statements and annual reports. The population consisted of 42 mining companies, while the sample was selected using purposive sampling, resulting in 27 companies or 81 firm-year observations. Financial statement fraud was measured using the F-Score, and the data were analyzed using multiple linear regression. The results show that pressure does not have a significant effect on financial statement fraud. In contrast, opportunity, rationalization, capability, ego, and collusion have significant effects on financial statement fraud. However, the effects of opportunity, capability, ego, and collusion tend to be negative, while rationalization shows a positive direction. These findings indicate that fraud hexagon elements do not operate uniformly in mining companies, and that proxy selection plays an important role in explaining financial statement fraud risk.